2004
DOI: 10.1017/s146114570400416x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the functional V158M catechol-O-methyl-transferase polymorphism with panic disorder in women

Abstract: Panic disorder is an anxiety disorder with an estimated heritability of up to 48%. Pharmacological and genetic studies suggest that genes coding for proteins involved in the catecholaminergic system might be relevant for the pathogenesis of the disease. In the present study, we genotyped a single nucleotide polymorphism (472G/A=V158M) in the coding region of the catechol-O-methyl-transferase (COMT) gene in 115 patients with panic disorder and age- and sex-matched controls. Association analysis revealed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
102
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 23 publications
13
102
0
1
Order By: Relevance
“…The fact that the positive result has not only been in the case-controls but also in the family sample is important evidence that population stratification is probably not creating a false positive result. Furthermore, these findings are consistent with two previous studies reporting an association of this more active COMT allele with PD, in particular in women (Domschke et al, 2004;Hamilton et al, 2002). Our findings are in line with a recent study on phobic Association of COMT with panic disorder C Rothe et al anxiety that has been reported to be associated with the valine allele of the functional COMT polymorphism in a sample of 1234 women (McGrath et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The fact that the positive result has not only been in the case-controls but also in the family sample is important evidence that population stratification is probably not creating a false positive result. Furthermore, these findings are consistent with two previous studies reporting an association of this more active COMT allele with PD, in particular in women (Domschke et al, 2004;Hamilton et al, 2002). Our findings are in line with a recent study on phobic Association of COMT with panic disorder C Rothe et al anxiety that has been reported to be associated with the valine allele of the functional COMT polymorphism in a sample of 1234 women (McGrath et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Ohara et al (1998) investigated a sample of anxiety disorder patients (n ¼ 108) including a small number of PD patients (n ¼ 29) and found no association. This small sample of PD patients had very low power to detect the COMT effect sizes observed in our study as well as in Domschke et al (2004) and Hamilton et al (2002). Furthermore, it is not clear whether matching of the control subjects concerning gender and age was carried out, since this information was not reported by the authors.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations